2023
DOI: 10.3389/fmars.2022.1045335
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation of cohesive sediments at the subtidal flat affected by wind wave in high turbidity estuary

Abstract: Sedimentation is an important mechanism to mitigate the shrinking of tidal flat and to restore its ecological function by means of sand or mud nourishment. To explore the sedimentation of cohesive sediments, a seabed tripod observation system was deployed at the subtidal region of the Hengsha Shoal adjacent to the turbidity maximum zone of the Yangtze Estuary for 11 days. The results showed that the fine sediment with the median grain size around 8 mm occupied the whole water column. The seabed was in relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…In studies of tidal flat sedimentary dynamics, many scholars have observed the impact of changes in wind conditions on tidal flat topography. The action of wind can affect the timing of tides, control resuspension processes, increase wave turbulence energy, and more (Christiansen et al, 2006;Talke and Stacey, 2008;Green, 2011;Colosimo et al, 2020;Shen et al, 2023). In extreme events such as typhoons or storm surges, this situation can worsen, as the intensification of winds and waves may increase wave trajectory speeds, consequently increasing the bed shear stress caused by waves.…”
Section: Bed Level Changementioning
confidence: 99%
“…In studies of tidal flat sedimentary dynamics, many scholars have observed the impact of changes in wind conditions on tidal flat topography. The action of wind can affect the timing of tides, control resuspension processes, increase wave turbulence energy, and more (Christiansen et al, 2006;Talke and Stacey, 2008;Green, 2011;Colosimo et al, 2020;Shen et al, 2023). In extreme events such as typhoons or storm surges, this situation can worsen, as the intensification of winds and waves may increase wave trajectory speeds, consequently increasing the bed shear stress caused by waves.…”
Section: Bed Level Changementioning
confidence: 99%